The effects of added protein to dry rolled and steam rolled sorghum grain fattening rations - Smith, E.F.; Richardson, D.; Cox, R.F.; Follis, D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Sorghum grain is used extensively in fattening rations for beef cattle. Its protein content reportedly varies from 6 to 12%. Wide differences in protein content result from variety, nitrogen supply in the soil, geographic location, moisture during a given year, and yield per acre. Interest is increasing in the varying protein content of sorghum grain. The main question is whether the protein in sorghum grain can satisfy the entire ration protein for fattening cattle. Objective of this experiment was to determine the value of adding various amount of soybean oil meal to dry-rolled and steam-rolled sorghum grain fattening rations for yearling heifers.
Keywords: Beef; Protein; Dry rolled; Steam rolled; Sorghum grain